Analysing Consumer Behavior for Healthy Food and Beverages to Create Marketing Strategy for Early-Stage Company (The Indonesian Journal of Business Administration, 2021)
The rise of awareness of links between food and health has been one of the most advanced social development in the past years. Health awareness related to food continues to rise as the availability of health information, technology, growing population, and increased risk for lifestyle disease also rise on the surface. The challenges faced by Temandni was shallow knowledge about the behaviour of the potential market. As the first step, research is conducted to analyze customer behaviour, and the research finding is aimed to evaluate and renew the marketing strategy.The research is a mix method study through the interview with 15 proposed interviewees and surveys from 215 respondents to gain insights for customer behaviour study. The qualitative study is used as an explorative study and continuous by confirmatory research used K-means cluster and ANOVA test for customer segmentation.According to the findings, it is founded that there are three different segments; cluster 1, cluster 2, and cluster 3. Each cluster has its characteristic. Cluster 1 is recommended to be chosen along with the recommendation on STP and mix marketing on Temandni. Keywords: Customer Behaviour, Healthy food, marketing strategy